Effects of tobacco cultivation on chemical properties of agricultural soils (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2021)
Tobacco is grown intensively in the North Western region of Bangladesh. The farmers in that region in Bangladesh receive less production of the next crop of tobacco and experience economical loss. We aimed to determine the impact of tobacco cultivation in soils. In order to determine the impact of tobacco cultivation in soil, 20 soil samples (10 from tobacco cultivated land and 10 from non-tobacco cultivated land) were collected from the study area. The samples were analyzed for soil pH, organic matter, humidity, macronutrients (N, P, K, S, Ca and Mg) and micronutrients (Zn, Fe, Mn, Cu and B). The concentration of available phosphorus (23.22 µg/g), total nitrogen (0.084 %), calcium (798 µg/g), magnesium (438 µg/g), zinc (1.00 µg/g), manganese (1.70 µg/g) boron (0.17 µg/g) including soil pH, organic matter and humidity showed higher values in tobacco cultivated land than those of the non-tobacco cultivated land. In contrast, concentration of total potassium (148.2 µg/g), available sulfur (5.45 µg/g), copper (2.40 µg/g) and iron (10.82 µg/g) in tobacco land showed lower values than those of the non-tobacco land. Soil magnesium level increased with increasing pH although the potassium level decreased with the increase of pH of the tobacco cultivated soils.